"عناصر الرضا "المفهوم والقياس : اطار فلسفي - د. جرجيس عمير عباس; أ.علاء عبد السلام اليماني; أ.منذر خضر المهتدي (PROSPECTIVE RESEARCHES, 2023)
This research aims at staying the concept of satisfaction, its items, and methods of measuring under a philosophical frame. Satisfaction, as other subject had been studied by some researchers, it can be considered as a result of the consumer's expectation about the goods, this expectation has a big deal about buying any kind of the goods. The organization which meet the acceptance of the buyers, has reached the concept of the satisfaction which is studied.